Structure of feeling in documentary theater and agitprop theater: experiences in Brazil and Argentina (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article approaches two theatrical experiences –one that can be theater of agitation and propaganda (agitprop) linked to the Landless Rural Workers Movement (MST), in Brazil, and a Documentary Theater carried out by the Ferrowhite  Museum-Workshop, in the Argentine city of Bahía Blanca – from the category of structure of feelings, created by the Marxist theorist and theater critic Raymond Williams. Through this category, it is sought that staging, when performed in circumscribed contexts or with specific social segments, can be understood as a mechanism for structuring community feelings, giving rise to counter-hegemonic cultural manifestations.
Keywords: documentary theater; agitprop theater; Raymond Williams; structure of feeling; staging